Adult height in patients with childhood onset atopic dermatitis. Issue 6 (1st June 1997) - Patel, Leena; Clayton, P E; Jenney, Meriel E M; Ferguson, Janice E; David, T J
Abstract : Cross sectional studies have reported impaired growth in children with atopic dermatitis. If this growth impairment is irreversible, it would be expected to adversely influence final height attainment. The standing heights and other anthropometric parameters were assessed in 35 adults with onset of atopic dermatitis before 5 years of age and a control group of 35 adults with adult onset contact dermatitis or psoriasis. There was no significant difference in the standing height SD score, mid-parental height SD score, sitting height SD score, subischial leg length SD score, nor body mass index between the atopic dermatitis and control groups. The standing height SD score was not significantly different among: (a) patients with atopic dermatitis affecting less than 50% of their body surface area and those with greater than 50% affected; (b) patients using the four different potency topical corticosteroids; and (c) patients with atopic dermatitis without asthma and those with coexisting asthma. It is concluded that short stature is not a feature of our group of adult patients with onset of atopic dermatitis before 5 years of age, continuing into adulthood, and severe enough to require specialist care. This suggests that if growth impairment occurs in childhood, it is likely to be temporary and reversible.